Effective HTCondor-based monitoring system for CMS - Balcas, J.; Bockelman, B. P.; Da Silva, J. M. [UNESP]; Hernandez, J.; Khan, F. A.; Letts, J.; Mascheroni, M.; Mason, D. A.; Perez-Calero Yzquierdo, A.; Vlimant, J. R. (IOP Publishing, 2017)
The CMS experiment at the LHC relies on HTCondor and glideinWMS as its primary batch and pilot-based Grid provisioning systems, respectively. Given the scale of the global queue in CMS, the operators found it increasingly difficult to monitor the pool to find problems and fix them. The operators had to rely on several different web pages, with several different levels of information, and sift tirelessly through log files in order to monitor the pool completely. Therefore, coming up with a suitable monitoring system was one of the crucial items before the beginning of the LHC Run 2 in order to ensure early detection of issues and to give a good overview of the whole pool. Our new monitoring page utilizes the HTCondor ClassAd information to provide a complete picture of the whole submission infrastructure in CMS. The monitoring page includes useful information from HTCondor schedulers, central managers, the glideinWMS frontend, and factories. It also incorporates information about users and tasks making it easy for operators to provide support and debug issues.